The Relationship of Student’s Readiness in Learning With Student’s Learning Achievement in History Class XI SMA Negeri Tegineneng - Ahmad Rudianto (FKIP UNIVERSITAS LAMPUNG, 2020)
ABSTRACT One of these factors is learning readiness. Based on the results of data analysis of research results and quantitative data analysis with correlation test and significance test, it was concluded that: